EFEKTIVITAS FILTER BIOCHAR PADA PENURUNAN KONSENTRASI AMMONIUM (NH₄⁺) DAN FOSFAT (PO₄³⁻) DALAM AIR LIMBAH - Shinta Enggar Maharani; Filemon Bram Gunas Junior; I Made Wahyu Wijaya (Fakultas Teknik Universitas Mahasaraswati Denpasar, 2026)
This study aimed to analyze the concentration trends of ammonium (NH₄⁺) and phosphate (PO₄³⁻) during 20 days of operation in a two-compartment biochar filtration system under continuous flow conditions, and to compare the performance of magnesium-activated biochar and non-activated biochar. Samples were collected daily from the influent (IN), effluent compartment 1 (EF1), and effluent compartment 2 (EF2). Concentrations were analyzed using spectrophotometric methods, and removal efficiency was calculated based on the difference between influent and effluent concentrations.The results showed that magnesium-activated biochar exhibited more effective and stable performance compared to non-activated biochar. For ammonium removal, activated biochar achieved efficiencies of 65–75%, while non-activated biochar only reached 30–60% and experienced a faster decline in performance due to media saturation. In terms of phosphate removal, activated biochar achieved efficiencies of 25–40% through Mg–PO₄ complex formation and micro-precipitation mechanisms. In contrast, non-activated biochar was ineffective and even showed negative removal efficiencies (-100% to -250%) due to phosphate leaching.Overall, magnesium activation significantly enhanced adsorption capacity, extended the effective operational period, and delayed media saturation in the continuous filtration system. Therefore, chemical modification of biochar is strongly recommended to improve nutrient removal performance in domestic wastewater treatment systems.